National spatiotemporal patterns of influenza-like illness in Iran: A pre-COVID-19 study (2015-2019). - Atieh Sedghian; Shahab MohammadEbrahimi; Benn Sartorius; Behzad Kiani (PLoS ONE)
Lower respiratory tract infections, including Influenza-Like Illness (ILI), contribute significantly to local and global mortality rates. This study aimed to identify high-risk areas for ILI incidence at the county level in Iran during the 4-year period prior to COVID-19. Data were analyzed from 109,167 ILI notifications collected between March 2015 and March 2019 through "The Iran Influenza Surveillance System (IISS)". Spatial scan statistics was utilized to identify significant spatial, temporal, and spatiotemporal clusters of ILI cases. The average age of patients was 40 years (range: 1-117), with females comprising 53% of cases. Males exhibited a higher significant case fatality rate (CFR= 3.28%) compared to females (CFR=2.46%)(P-value<0.05). Among all patients, 53% were tested for influenza, and 22% of those tested had a confirmed case, which accounts for 12% of all ILI patients, with Type A being the predominant strain, accounting for 79.15% of cases. Type A influenza had a higher CFR than type B (5.4% vs. 3.01%, respectively). Among the A virus subtypes, H1N1 exhibited the highest CFR at 8.06%. During the study period, from December 2015 to February 2016, provinces such as Khuzestan, Fars, Kerman, and Yazd reported the highest incidence of ILI. Similarly, the provinces of Alborz, Tehran, and Gilan also experienced elevated ILI rates. In contrast, the period from April 2015 to October 2015 saw the lowest incidence of ILI. Notably, the highest CFR was recorded during the months with the peak ILI incidence. The incidence of ILI fluctuated significantly, peaking at 42.04 in the first year, falling to 24.12 in the second year, and continuing to vary in the following years. These findings underscore the urgent need for tailored public health interventions, such as enhanced surveillance and targeted vaccination campaigns, in provinces where ILI incidence and mortality are highest. By concentrating resources and efforts in these high-risk areas, it may be possible to more effectively manage and control ILI outbreaks.